Spin-transfer torque effects in the dynamic forced response of the magnetization of nanoscale ferromagnets in superimposed ac and dc bias fields in the presence of thermal agitation - Byrne, D J; Coffey, W T; Kalmykov, Y P; Titov, S V; Wegrowe, J E (arXiv.org, 2015)
Spin-transfer torque (STT) effects on the stationary forced response of nanoscale ferromagnets subject to thermal fluctuations and driven by an ac magnetic field of arbitrary strength and direction are investigated via a generic nanopillar model of a spin-torque device comprising two ferromagnetic strata representing the free and fixed layers and a nonmagnetic conducting spacer all sandwiched between two ohmic contacts. The STT effects are treated via the Brown magnetic Langevin equation generalized to include the Slonczewski STT term thereby extending the statistical moment method [Y. P. Kalmykov et al., Phys. Rev. B 88, 144406 (2013)] to the forced response of the most general version of the nanopillar model. The dynamic susceptibility, nonlinear frequency-dependent dc magnetization, dynamic magnetic hysteresis loops, etc. are then evaluated highlighting STT effects on both the low-frequency thermal relaxation processes and the high-frequency ferromagnetic resonance, etc., demonstrating a pronounced dependence of these on the spin polarization current and facilitating interpretation of STT experiments.